Using Some Visual Means in Eeducation-Some Arabic Grammatical Methods as A Sample - Mohammed, Sabah H.; Ahmed Ezzat, Azza A. (Humanities Journal of University of Zakho, 2013)
Our students in the Kurdistan Area experience many educational difficulties in their classes. One of the most common obstacles is coping with the Arabic language as it is not their mother tongue. Other than its grammatical challenges, the study of Arabic is a cumulative study that cannot be understood, memorized, and learned very quickly by the students who wish to master it. The problem would be more of an issue for those who study it as a second language. Next, the students need somebody to help them to understand how to summarize the hand-outs and study them. Many students usually ask: What will the exam questions be like? What areas should we concentrate on?? How should we study the materials? Some teachers may use colors to explain. Some might circle and underline what s/he thinks is worth focusing on This is undoubtedly helpful. In this research, we tried to show how important it is for students to grasp their class materials visually. We did this by using colors, bolding, and underlining several words. This was supported by many examples, tables, and graphs which provided a general idea and a high level view about the studied subject. This method would be more effective if it were presented using MS PowerPoint. Because of the diversity of students’ attitudes regarding teaching methods, we found that the teaching method which uses charts, tables, and graphs with various editing means - such as bolding some words and underlining others – was more helpful for students. It helps them to learn how to summarize the allocated materials, how to concentrate on its essentials, and how to compare between their similar parts. It seems to us that the importance of such things is not restricted to Natural Sciences, but it is important for humanities as well. Using such methods and clarifying formats cannot be used arbitrarily. They should be used with some scientific planning such as using gradual levels of colors for headings and subheadings. The same thing applies to the font size and bolding of text. As for underlining important words, it undoubtedly draws attention to important rules or exceptions, for example. To compensate for a lack of color printing, we used formatting techniques such as bolding and underlining. Our way of teaching was confirmed through our lectures and research about Arabic writing rules, Arabic classes of speech and vocalization, and Arabic prosody. In fact, we used such methods in our exam papers as well. We discovered that using tables, charts, and formatting in the exam paper also makes it easy to read, to answer, and to correct. We tried to include as much information as possible in those tables and trees in addition to many notes in order to attract the students’ attention to the numerous things we wanted to emphasize .